Preparation method of high-permeability TPMS structural ceramic membrane

The method addresses the low porosity and high permeation resistance of ceramic membranes by creating a TPMS structural silicon carbide ceramic membrane with a three-dimensional interconnected pore structure and controllable separation layer, enhancing permeability and stability for efficient high-temperature dust removal.

CN119219425APending Publication Date: 2024-12-31NANJING TECH UNIV

Patent Information

Application Number
CN202411347229.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Ceramic membranes used in high-temperature dust removal applications suffer from low porosity, high pore tortuosity, and interlayer infiltration, leading to high permeation resistance and reduced efficiency.

Method used

A method involving photocurable ceramic slurry preparation, 3D printing, and one-step debinding-sintering process to create a TPMS structural silicon carbide ceramic membrane with a three-dimensional interconnected pore structure and controllable separation layer thickness.

Benefits of technology

The method results in a highly permeable ceramic membrane with reduced permeation resistance, improved stability at high temperatures, and enhanced separation efficiency for high-temperature dust removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219425A_ABST
    Figure CN119219425A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a TPMS structural ceramic membrane with high air permeability. The TPMS structural ceramic membrane is prepared by taking the ceramic slurry as a raw material and adopting photocuring 3D printing forming and high-temperature sintering. A digital model of a TPMS structural ceramic membrane is constructed on the basis of a three-period TPMS structure, the ceramic membrane is composed of a TPMS porous structure supporting body and a thickness-controllable separation layer, and the TPMS structural supporting body prepared through 3D printing remarkably reduces the permeation resistance of the ceramic membrane through high porosity and low pore channel tortuosity of the TPMS structural supporting body. The TPMS structural ceramic membrane is formed at a time through photocuring 3D printing and formed through one-time sintering, the preparation period is effectively shortened, and sintering energy consumption is reduced. The prepared TPMS structural ceramic membrane is high in air permeability, uniform and controllable in pore structure and good in stability in a high-temperature environment, and an efficient material is provided for high-temperature gas dust removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-permeability TPMS structural ceramic membrane, and belongs to the field of membrane material preparation. Background Art

[0002] The process industry is often accompanied by a large amount of high-temperature dusty flue gas. High-temperature flue gas is not only high in temperature and high in dust content, but also has certain acid-base corrosiveness. The efficient treatment of high-temperature flue gas is of great significance to both the environment and production. Ceramic membrane high-temperature dust removal technology has mechanical and chemical stability in high-temperature flue gas environments, and can maintain good dust removal effects. Ceramic membranes are usually composed of a support, a transition layer, and a separation layer, but problems such as low porosity, high pore tortuosity, and interlayer infiltration make the permeation resistance of ceramic membranes high, affecting their application efficiency in the separation field. Therefore, improving the structure of ceramic membranes is of great significance for the preparation of highly permeable high-temperature dust removal ceramic membranes.

[0003] 3D printing (“additive manufacturing”) is a manufacturing technology that converts digital models into physical parts by accumulating materials layer by layer. It has significant advantages over “equivalent material manufacturing” and “subtractive manufacturing” technologies in the field of complex structural parts preparation. Photocuring 3D printing technology has the advantages of high molding accuracy, fast speed, diverse materials, and flexible structure. Photocuring 3D printing ceramic molding technology usually mixes ceramic powder with photosensitive resin, prints it first, and then undergoes a debinding-sintering process to obtain ceramic materials. Chen et al. [Ceramics International 50 (2024) 1732–1741] used DLP-3D printing technology to prepare porous alumina ceramics. Shi et al. [Additive Manufacturing 79 (2024) 103942] used DLP-3D printing technology to successfully prepare high-performance silicon carbide ceramic materials with high density and flexural strength of more than 200 MPa.

[0004] The TPMS structure is a minimal surface structure that is periodic in three independent directions in three-dimensional space after being optimized by mathematical models. It has a high specific surface area and a three-dimensionally connected porous structure. Sun et al. [ACS Appl. Mater. Interfaces 2020, 12, 34837−34847] prepared a Gyroid structure Au-CuS material for solar steam power generation based on the advantages of the high-density three-dimensional structure of the TPMS structure in high-efficiency light energy conversion, achieving a dynamic balance of water absorption and evaporation in nanochannels and efficient heat conduction. Sreedhar et al. [Desalination 425 (2018)12–21] prepared a TPMS structure feed gasket for water treatment processes, which showed good anti-fouling performance and permeation flux in both reverse osmosis and ultrafiltration membrane separation. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a highly permeable TPMS structural ceramic membrane. The ceramic membrane prepared by the present invention has a three-dimensional interconnected pore structure that can be precisely controlled, and a separation layer with controllable thickness. The one-step molding and one-time sintering preparation process greatly shortens the production cycle. The prepared TPMS structural ceramic membrane has good permeability flux and exhibits good separation efficiency in high-temperature dust removal.

[0006] The technical solution of the present invention is: A method for preparing a silicon carbide ceramic membrane of a TPMS structure, the specific steps of which are as follows: A. Preparation of photocurable porous ceramic slurry: Place photosensitive resin and ceramic powder photoinitiator in a ball mill according to a certain ratio, mix them evenly at a certain speed, and then defoam the mixed ceramic slurry through mechanical stirring to obtain photocurable ceramic slurry.

[0007] B. Modeling of TPMS structural ceramic membrane: establish a digital model of the TPMS structural ceramic membrane through 3D modeling software, import the implicit function formula of the TPMS structure into nTop 3D modeling software, construct the TPMS structural unit, set the unit size and wall thickness parameters of the TPMS structural unit; then construct the ceramic membrane model, set its diameter and thickness parameters, couple the TPMS structural unit with the ceramic membrane, and obtain the digital model of the TPMS structural ceramic membrane, including the TPMS structural support body and the separation layer.

[0008] C. 3D printing of TPMS structural silicon carbide ceramic membrane green body. The TPMS structural ceramic membrane model is imported into the software associated with the 3D printer in the form of an STL file. The slice thickness, exposure intensity and other parameters of the printing process are set. The ceramic membrane green body is prepared through a photocuring 3D printing process. After printing is completed, the printed silicon carbide ceramic membrane green body is removed from the printing platform, the slurry remaining on the surface of the green body is cleaned with a cleaning agent and dried at a certain temperature.

[0009] D. Sintering of TPMS structural ceramic membrane: placing the TPMS structural ceramic membrane green body in a high-temperature sintering furnace, setting the heating rate and holding time of the debinding-sintering process, and cooling with the furnace after sintering.

[0010] Preferably, the ceramic powder content in the ceramic slurry is 50-60 wt%, the added amount of the photoinitiator is 0.5-1 wt%, and the rest is photosensitive resin.

[0011] Preferably, in the preparation of the ceramic slurry, the ball milling speed is 350-450 rpm, and the ball milling time is 4-6 h; the mechanical stirring speed is 300-500 rpm, and the mixing time is 1-2 h.

[0012] Preferably, the TPMS structural unit includes a Diamond structure (D), a Gyorid structure (G), a Permitive structure (P), and a Split-P structure.

[0013] Preferably, the size of the TPMS structural unit is 1.0-5.0 mm, and the wall thickness of the structural unit is 0.1-2 mm.

[0014] Preferably, the separation layer thickness of the TPMS structure sheet ceramic membrane is 50-200 μm.

[0015] Preferably, the slice thickness during the photocuring process is 25-50 μm, and the exposure intensity is 150-250 mJ / cm 2 .

[0016] Preferably, the cleaning agent in the cleaning process is 1,6-hexanediol diacrylate (HDDA) and deionized water, and the drying process is drying at 25° C. for 6 hours.

[0017] Preferably, the debinding sintering temperature of the silicon carbide ceramic membrane green body is 300-600°C, the debinding time is 2-6 h, and the heating rate is 0.5-1.5°C / min.

[0018] Preferably, the sintering temperature of the silicon carbide ceramic film is 1300-1500°C, the sintering time is 2-4 h, and the heating rate is 1-3°C / min.

[0019] The beneficial effects of the present invention are: The present invention uses photocurable ceramic slurry as raw material, adopts photocurable 3D printing to prepare ceramic membrane green body, and then obtains TPMS structural ceramic membrane through debinding-sintering process. Based on the three-periodic minimal surface (TPMS) structure, combined with three-dimensional modeling software, a digital model of TPMS structural ceramic membrane is constructed. The highly permeable ceramic membrane is composed of a support body of TPMS porous structure and a separation layer with controllable thickness. The 3D-printed TPMS structural support body significantly reduces the permeation resistance of the ceramic membrane with its high porosity and low pore tortuosity. At the same time, the TPMS structural ceramic membrane is formed in one time by photocuring 3D printing and sintered in one time, which effectively shortens the preparation cycle and reduces the sintering energy consumption. The TPMS structural ceramic membrane prepared by the present invention has high permeability, uniform and controllable pore structure, good stability in high temperature environment, and provides a high-efficiency material for high-temperature gas dust removal. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the Gyroid structure ceramic membrane of Example 3 of the present invention.

[0021] Figure 2 This is a real picture of the Gyorid structural ceramic membrane green body prepared in Example 3 of the present invention.

[0022] Figure 3 This is a photo of the Gyorid structure ceramic membrane after sintering prepared in Example 3 of the present invention.

[0023] Figure 4 The microscopic morphology of the Gyroid structure ceramic membrane prepared in Example 3 of the present invention.

[0024] Figure 5 The pore size distribution and gas flux of the Gyroid structure ceramic membrane prepared in Example 3 of the present invention.

[0025] Figure 6 The air permeability of the Gyroid structural ceramic membrane prepared in Example 3 of this invention is compared with that of other research works (3D printed symmetrical structural ceramic membrane and extruded ceramic membrane). DETAILED DESCRIPTION Example 1

[0026] The ceramic powder content in the ceramic slurry is 50wt%, the amount of photoinitiator added is 0.5wt%, and the rest is photosensitive resin. First, 50 wt% ceramic powder is added to the photosensitive resin, and the mixture is mixed at 400 rpm for 4 h by ball milling. Then, 0.5 wt% photoinitiator is added, and the mixture is mixed at 500 rpm for 30 min by mechanical stirring to obtain a homogeneous ceramic slurry. The TPMS structure is constructed by implicit function modeling. The implicit function formula of the Gyroid structure is imported into the nTop 3D modeling software. The unit size of the Gyroid structure unit is set to 1.0 mm and the wall thickness parameter is set to 0.1 mm to generate the basic structural unit of the Gyroid structure. Then, the ceramic membrane model is constructed, and the diameter is set to 30 mm and the thickness is set to 3 mm. The Gyroid basic structural unit is coupled with the ceramic membrane to obtain the digital model of the Gyroid structure ceramic membrane, in which the separation layer thickness is 200 μm. The Gyroid structure ceramic membrane model file was imported into the 3D printing slice software. During the photocuring process, the slice thickness was set to 50 μm and the single layer exposure intensity was set to 150 mJ / cm 2 . After printing, the model was removed from the printing platform, the green body was cleaned with HDDA resin and deionized water, and dried at 25 °C for 6 h. In an air atmosphere, the temperature was raised to 300 °C at a heating rate of 0.5 °C / min and kept for 6 h to allow the resin to fully decompose, and then the temperature was raised to 1300 °C at a heating rate of 1 °C / min and kept for 2 h. The prepared silicon carbide porous ceramic membrane has an average pore size of 3.7 μm, a porosity of about 85%, and a gas permeability of 600 m 3 / (m 2 ·h·kPa). Example 2

[0027] The ceramic powder content in the ceramic slurry is 60 wt%, the amount of photoinitiator added is 1 wt%, and the rest is photosensitive resin. First, 60 wt% ceramic powder is added to the photosensitive resin, and the mixture is mixed at 500 rpm for 6 h by ball milling. Then, 1 wt% photoinitiator is added, and the mixture is mixed at 800 rpm for 60 min by mechanical stirring to obtain a homogeneous ceramic slurry. The TPMS structure is constructed by implicit function modeling. The implicit function formula of the Gyroid structure is imported into the nTop 3D modeling software. The unit size of the TPMS structure unit is set to 5.0 mm and the wall thickness parameter is set to 1.0 mm to generate the basic structural unit of the Gyroid structure. Then, the ceramic membrane model is constructed, and the diameter is set to 30 mm and the thickness is set to 3 mm. The Gyroid basic structural unit is coupled with the ceramic membrane to obtain the digital model of the Gyroid structure ceramic membrane, in which the separation layer thickness is 100 μm. The TPMS structural ceramic membrane model file was imported into the 3D printing slicing software. During the photocuring process, the slice thickness was set to 25 μm and the single layer exposure intensity was set to 250 mJ / cm. 2 . After printing, the model was removed from the printing platform, the green body was cleaned with HDDA resin and deionized water, and dried at 25 °C for 6 h. In an air atmosphere, the temperature was raised to 600 °C at a heating rate of 1.5 °C / min and kept for 6 h to fully decompose the resin, and then the temperature was raised to 1500 °C at a heating rate of 3 °C / min and kept for 4 h. The prepared silicon carbide porous ceramic membrane has an average pore size of 2.5 μm, a porosity of about 70%, and a gas permeability of 600 m 3 / (m 2 ·h·kPa). Example 3

[0028] The ceramic powder content in the ceramic slurry is 55 wt%, the amount of photoinitiator added is 0.75 wt%, and the rest is photosensitive resin. First, 55 wt% ceramic powder is added to the photosensitive resin, and the mixture is mixed at 450 rpm for 5 h by ball milling. Then, 0.75 wt% photoinitiator is added, and the mixture is mixed at 600 rpm for 60 min by mechanical stirring to obtain a homogeneous ceramic slurry. The TPMS structure is constructed by implicit function modeling. The implicit function formula of the Gyroid structure is imported into the nTop 3D modeling software. The unit size of the Gyroid structure unit is set to 1.5 mm and the wall thickness parameter is set to 0.25 mm to generate the basic structural unit of the Gyroid structure. Then, the ceramic membrane model is constructed, and the diameter is set to 30 mm and the thickness is set to 3 mm. The Gyroid basic structural unit is coupled with the ceramic membrane to obtain the digital model of the Gyroid structure ceramic membrane, in which the separation layer thickness is 50 μm. The Gyroid structure ceramic membrane model file was imported into the 3D printing slice software. During the photocuring process, the slice thickness was set to 25 μm and the single layer exposure intensity was set to 200 mJ / cm 2 . After printing, the model was removed from the printing platform, the green body was cleaned with HDDA resin and deionized water, and dried at 25 °C for 6 h. In an air atmosphere, the temperature was raised to 600 °C at a heating rate of 0.75 °C / min and kept warm for 4 h to allow the resin to fully decompose, and then the temperature was raised to 1400 °C at a heating rate of 2.5 °C / min and kept warm for 2 h. The prepared silicon carbide porous ceramic membrane has an average pore size of 2.5 μm, a porosity of about 83%, and a gas permeability of 550 m 3 / (m 2 ·h·kPa).

[0029] Figure 1 It is a digital model of the Gyroid structural ceramic membrane prepared in this embodiment. The Gyroid structural ceramic membrane consists of a separation layer and a Gyroid structural support body, wherein the Gyroid structural support body is composed of a plurality of Gyroid basic structural units arranged in a periodic manner. The Gyroid basic structural unit is defined by the unit size and the unit wall thickness, and the ceramic membrane is defined by the diameter, the support body thickness and the membrane layer thickness. Figure 2 and Figure 3 They are respectively the green body and the actual pictures of the Gyroid structural ceramic membrane prepared in this embodiment after sintering. The green body of the Gyroid structural ceramic membrane formed by 3D printing is consistent with the digital model, and the microstructure forming accuracy is high. The structure has no deformation after sintering and has good strength. Figure 4 This is the microscopic morphology of the Gyroid structure ceramic membrane prepared in this example. The thickness of the ceramic membrane separation layer is about 80 μm, and the thickness of the support body wall is about 250 μm, which is consistent with the digital model parameters. Figure 5The pore size distribution and gas flux of the Gyroid structure ceramic membrane prepared in this example have good pore size distribution concentration, the main pore size is about 4.0 μm, and the gas flux is about 550 m 3 / (m 2 ·h·kPa). Figure 6 It is the relationship between the Darcy permeability and pore size of the Gyroid structural ceramic membrane prepared in this example and the ceramic fiber membrane prepared in other research works (3D printed symmetrical structure ceramic membrane, traditional extrusion molded ceramic membrane). When the membrane pore sizes are similar, the Darcy permeability coefficient of the Groid structural ceramic membrane is significantly higher than that of the 3D printed ceramic membrane without TPMS structure and the ceramic membrane prepared by extrusion molding. It can be seen that the air permeability of the Groid structural ceramic membrane prepared by the present invention is better than the average level. Example 4

[0030] The ceramic powder content in the ceramic slurry is 55 wt%, the amount of photoinitiator added is 0.75 wt%, and the rest is photosensitive resin. First, 55 wt% ceramic powder is added to the photosensitive resin, and the mixture is mixed at 450 rpm for 5 h by ball milling. Then, 0.75 wt% photoinitiator is added, and the mixture is mixed at 600 rpm for 60 min by mechanical stirring to obtain a homogeneous ceramic slurry. The TPMS structure is constructed by implicit function modeling. The implicit function formula of the Diamond structure is imported into the nTop 3D modeling software. The unit size of the Diamond structure unit is set to 2.5 mm and the wall thickness parameter is set to 0.5 mm to generate the basic structural unit of the Diamond structure. Then, the ceramic membrane model is constructed, and the diameter is set to 30 mm and the thickness is set to 3 mm. The Diamond basic structural unit is coupled with the ceramic membrane to obtain the Gyroid structure ceramic membrane digital model, in which the separation layer thickness is 50 μm. The Diamond structural ceramic membrane model file was imported into the 3D printing slice software. During the photocuring process, the slice thickness was set to 25 μm and the single layer exposure intensity was set to 200 mJ / cm 2 . After printing, the model was removed from the printing platform, the green body was cleaned with HDDA resin and deionized water, and dried at 25 °C for 6 h. In an air atmosphere, the temperature was raised to 600 °C at a heating rate of 0.75 °C / min and kept for 4 h to allow the resin to fully decompose, and then the temperature was raised to 1400 °C at a heating rate of 2.5 °C / min and kept for 2 h. The prepared silicon carbide porous ceramic membrane has an average pore size of 2.6 μm, a porosity of about 80%, and a gas permeability of 520 m 3 / (m 2 ·h·kPa). Example 5

[0031] The ceramic powder content in the ceramic slurry is 55 wt%, the amount of photoinitiator added is 0.75 wt%, and the rest is photosensitive resin. First, 55 wt% ceramic powder is added to the photosensitive resin, and the mixture is mixed at 450 rpm for 5 h by ball milling, and then 0.75 wt% photoinitiator is added, and the mixture is mixed at 600 rpm for 60 min by mechanical stirring to obtain a homogeneous ceramic slurry. The TPMS structure is constructed by implicit function modeling. The implicit function formula of the Permitive structure is imported into the nTop 3D modeling software. The unit size of the Permitive structure unit is set to 2.5 mm and the wall thickness parameter is set to 0.5 mm to generate the basic structural unit of the Permitive structure. Then, the ceramic membrane model is constructed, and the diameter is set to 30 mm and the thickness is set to 3 mm. The Permitive basic structural unit is coupled with the ceramic membrane to obtain the Gyroid structure ceramic membrane digital model, in which the separation layer thickness is 50 μm. The Permitive structural ceramic membrane model file was imported into the 3D printing slice software. During the photocuring process, the slice thickness was set to 25 μm and the single layer exposure intensity was set to 200 mJ / cm 2 . After printing, the model was removed from the printing platform, the green body was cleaned with HDDA resin and deionized water, and dried at 25 °C for 6 h. In an air atmosphere, the temperature was raised to 600 °C at a heating rate of 0.75 °C / min and kept for 2 h to fully decompose the resin, and then the temperature was raised to 1400 °C at a heating rate of 2.5 °C / min and kept for 2 h. The prepared silicon carbide porous ceramic membrane has an average pore size of 2.4 μm, a porosity of about 81%, and a gas permeability of 505 m 3 / (m 2 ·h·kPa).

Claims

1. A method for preparing a highly permeable TPMS structural ceramic membrane, characterized in that: The preparation method comprises the following steps: A. Preparation of photocurable silicon carbide porous ceramic slurry: Place photosensitive resin, ceramic powder and photoinitiator in a ball mill according to a certain ratio, mix them evenly at a certain speed, and then defoam the mixed ceramic slurry by mechanical stirring to obtain photocurable ceramic slurry; B. Modeling of TPMS structural ceramic membrane: Establish a digital model of TPMS structural ceramic membrane through 3D modeling software, import the implicit function formula of TPMS structure into nTop 3D modeling software, construct TPMS structural unit, set the unit size and wall thickness parameters of TPMS structural unit; then construct the ceramic membrane model, set its diameter and thickness parameters, couple the TPMS structural unit with the ceramic membrane, and obtain the digital model of TPMS structural ceramic membrane, including TPMS structural support body and separation layer; C. 3D printing of TPMS structural silicon carbide ceramic membrane green body: import the TPMS structural ceramic membrane model into the software associated with the 3D printer in the form of an STL file, set the slice thickness, exposure intensity and other parameters of the printing process, and prepare the ceramic membrane green body through the light-curing 3D printing process; After printing is completed, the printed silicon carbide ceramic membrane green body is removed from the printing platform, the slurry remaining on the surface of the green body is cleaned with a cleaning agent and dried at a certain temperature; D. Sintering of TPMS structural ceramic membrane: placing the TPMS structural ceramic membrane green body in a high-temperature sintering furnace, setting the heating rate and holding time of the debinding-sintering process, and cooling with the furnace after sintering.

2. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: The ceramic powder content in the ceramic slurry is 50-60 wt%, the added amount of the photoinitiator is 0.5-1 wt%, and the rest is photosensitive resin.

3. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: In the preparation of ceramic slurry, the ball milling speed is 300~500 rpm, and the ball milling time is 4~6 h; the mechanical stirring speed is 500~800 rpm, and the mixing time is 30~60 min.

4. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: TPMS structural units include Diamond structure (D), Gyorid structure (G), Permitive structure (P), and Split-P structure.

5. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: In the TPMS structural unit, the unit size is 1.0~5.0 mm, and the unit wall thickness is 0.1~1 mm.

6. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: The separation layer thickness of the TPMS structure sheet ceramic membrane is 50~200 μm.

7. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: During the photocuring process, the slice thickness was 25-50 μm and the exposure intensity was 150-250 mJ / cm 2 .

8. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: The cleaning agent in step C is 1,6-hexanediol diacrylate (HDDA) and deionized water, and the drying process is drying at 25° C. for 6 h.

9. The method for preparing a highly permeable TPMS structural ceramic membrane according to claim 1, characterized in that: The temperature of the debinding process of the TPMS structural ceramic membrane green body is 300~600 ℃, the heating rate is 0.5~1.5 ℃ / min, and the holding time is 2~6 h; the heating rate of the sintering process of the silicon carbide ceramic membrane is 1~3 ℃ / min, the sintering temperature is 1300~1500 ℃, and the holding time is 2~4 h.

Citation Information

Patent Citations

  • Preparation method of porous silicon carbide ceramic based on P curved surface

    CN109516810A

  • Preparation method of porous extremely small curved structure aluminum oxide ceramics based on 3D printing

    CN109665819A

Cited By

  • Sketch type tent design method based on minimal curved surface

    CN119942026A

  • Preparation method of aluminum oxide flat plate ceramic membrane

    CN121135388A

  • Preparation method of photocuring 3D printed FCC structure high-flux SiC catalytic membrane

    CN121972193A